Pt-promoted HY@KCC-1 as a highly selective catalyst for hydroisomerization of n-dodecane with enhanced mass transfer limitation. - Y., Gambo; A. A., Jalil; S., Triwahyono; S. M., Izan; A. A., Abdulrasheed; Mastura, Ibrahim; Herma Dina, Setiabudi (2018)
A unique core-shell fibrous silica zeolite HY (HY@KCC-1) catalyst with high surface area of 568 m2/g was successfully synthesized via a facile silica solvothermal procedure coupled with zeolite crystalseed crystallization, and subsequently investigated for n-dodecane hydroisomerization. Field Emission Scanning Microscope (FESEM) combined with X-ray Diffraction (XRD) revealed the fibrous silica growth. Probing of the Brønsted (BAS) and Lewis (LAS) acid sites with 2,6-dimethylpyridine (2,6-DMP) via Fourier Transform Infrared Spectroscopy (FT-IR) revealed that Pt/HY@KCC-1 had abundant strong acid sites with improved accessibility relative to unmodified Pt/HY catalyst. The Pt/HY@KCC-1 has displayed complete n-dodecane conversion coupled with an incredibly enhanced isomer yield of 72 % at 350 oC, nearly two-fold higher than unmodified Pt/HY catalyst. Additionally, the unique morphology and increased mesopores on Pt/HY@KCC-1 led to the superb catalytic activity via enhanced acid site accessibility by bulky n-dodecane reactant molecules and easy desorption of product isomers prior to being cracked. Remarkably, Pt/HY@KCC-1 had an internal effectiveness factor (η) of unity, thus suggesting its potential application in hydroisomerization of higher hydrocarbons for enhancing fuel properties